Farming for socio-ecological resilience: Understanding factors influencing the adoption of integrated farming systems among organic farmers in Northeast Thailand - Chaiteera Panpakdee; Suwannee Hoaihongthong (Social Sciences and Humanities Open, 2025)
Integrated Farming Systems (IFS), often integrated with organic agriculture, refer to diversified farming systems that combine crop cultivation, livestock production, and other complementary enterprises within a single farm unit. Despite increasing recognition in Thailand as a sustainable strategy, the adoption of IFS among organic farmers remains heterogeneous, with its drivers and constraints remaining underexplored. This study clarifies the socio-ecological factors influencing the adoption of IFS among 11 organic farmers purposively selected across four provinces in Northeast Thailand, employing an integrated theoretical framework and a thematic analysis of farm observations and interviews. Three core findings emerged: First, peer-to-peer learning and perceived usefulness accelerate IFS adoption, with farmers relying more heavily on horizontal knowledge transfer than formal extension services. Second, resource access, particularly fragmented landholdings and degraded soils, presents barriers to implementation. Third, institutional support mechanisms remain inadequate in addressing the socio-ecological contexts of farmers, creating gaps between policy intentions and on-the-ground realities that limit scaling potential. These findings highlight the need for integrative policy schemes that prioritize farmer-to-farmer knowledge networks, address structural land constraints, and align institutional support with localized farming contexts.